Estimating the Prevalence of Asymptomatic Cases of Covid-19 in Our Communities - Comiskey, Catherine (Statistical and Social Inquiry Society of Ireland, 2020)
Resource planning in healthcare is dependent on many factors from the scale of the health challenge to the available human and infrastructural resources. With the sudden and unforeseen scale of the Covid-19 pandemic across the globe, health ministries, policy makers and professionals were challenged to react with speed and commitment. Many rose to this challenge and the initial containment of the spread of the virus was achieved where leadership within communities was clear, consistent and most importantly well informed.
read before the Society, 21st May 2020 - SSISI Public Policy Brief: Understanding the Covid19 Pandemic and its Consequences
Keywords: 314.15